Pengaruh Model Think Pair Share Terhadap Hasil Belajar Siswa Materi IPS Kelas V SD Negeri 11 Palembang - Herawati, Sapta; Hetilaniar, Hetilaniar; Nurhasana, Putri Dewi (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of the think pair share model on learning outcomes that can improve the learning outcomes of fifth grade students at SD Negeri 11 Palembang. This research is a quantitative research using experimental method of Quasi experimental research with Posttest-Only Control Design. The variables in this study consisted of the independent variable (X) namely the thinkpair share model and the dependent variable (Y) namely learning outcomes. The research population was all fifth grade students of SD Negeri 11 Palembang, totaling 72 students. The sampling technique used is purposive sampling. The sample in this study was grouped into the experimental class (VA totaled 23 students) and the control class (VB totaled 23 students). Data collection techniques using tests, documentation and interviews. The data analysis technique used t-test independent sample t-test. The results of the experimental group research obtained an average value of 77.83 and the control groupobtained an average posttest score of 63.47. The results of the t_count test are 5.524 with t_(table ) 1.680 with a degree of freedom of 0.05, meaning that it can be concluded that there is an influence of the think pair share model on student learning outcomes for social studies material for class V SD Negeri 11 Palembang.